Effects of cell immobilization to the phytate-degrading enzyme activity - Mohamad Puad, Noor Illi; Farouk, Abd Alaziem; Salleh, Hamzah Mohd. (IIUM Press, 2011)
The use of immobilized whole microhial cells and/or organelles eliminates lhc often tedious. lime consuming. and expensi\'e sleps invohed in isolation and purificatioll of imraccllular enzymes. II al>o lends 10 enhance the stability of lhe enzyme by relaining its nall.....l catalytic surroundings during immobilizalion and subsequent cominuous operalion. A baclerium isolated from Malaysian waslewatn pnxlucing a 1l0,-e1 phyrate-degrading enzyme namely PhyFAUIAI was immobilized in alginate gel beads. PhyFAUIA 1 is a periplasmatic enzyme and highly substralespecific 10 phytale. The enzyme aClivity wa~ invesligaled upon cell immobilization. No shift in pH oplima of phytase of immobilized cells was obsen·ed. 110wever. the optimum lcmperaturcbwas shifted 10 50°C, which was 15°C lower lhan free PhyFAUIAI enzyme. Immobilized cells were found 10 be more stable in wider range of pll and tcmpe-ramr.: compared to free cells. The results presenled in this work show lhe potential for using immobilized cells to produce ditrerent "~nJ-inosilOl phosphates intennediales